The Effect of Digital Quran Reading on Gadget Addiction Behavior in Early Adulthood Individuals in Palembang City - Silvia Afnes; Annisa Syifa Azzahra; Jingga Rahmadona; Richard Dunde; Nico Satria; Jorgi Mahendra; Ayu Arfa Sari; Nabila Fatricia; Layla Shallma Putri Pracia (CV. Doki Course and Training, 2025)
Gadget is a mini mechanical device or tool or an interesting tool. gadgets have both positive and negative impacts on anyone who wears them. This study is a quantitative study using two variables, namely reading the Quran as an independent variable and Gadget addiction as a dependent variable with a quasi-experimental method with Pretest-posttest control group Design, this study uses a survey technique that is filling the gadget addiction scale questionnaire with a sample of 30 male and female subjects who were divided into two groups, namely the control group that was not given treatment and the experimental group that was given treatment in the form of digital Al - Quran reading treatment. Based on the output table above, the value of Asymmp Sig is known. (2-tailed) in the control group of (0.801 > 0.05), then H0 is accepted and Ha is rejected. So, it can be concluded that there is no difference in the average value of pre-test and post-test in the control group, which means there is no change in the group that was not given treatment. While the value of Asymmp Sig. (2-tailed) in the experimental group of (0.161 > 0.05), then H0 is accepted and Ha is rejected. So it can be concluded that there is no difference in the average value of pretest and posttes in the experimental group which means there is no change in the group given treatment in the form of treatment of digital Quran reading in early adult individuals with an age range of 18-22 years in the city of Palembang.